KUALITAS PELAYANAN SURAT KETERANGAN GANTI RUGI (SKGR) PADA KANTOR CAMAT TEMBILAHAN HULU - RIAU - jurnalmap map (MAP (Jurnal Manajemen dan Administrasi Publik), 2022)
This study aims to analyze the mechanism for providing compensation certificates (SKGR) at the Tembilahan Hulu District Office. To achieve this goal, a quantitative descriptive analysis technique is used for services according to the MENPAN Decree Number 63 of 2003 concerning General Guidelines for the Implementation of Public Services.The results of the research from the ten service mechanisms, most of the respondents' answers were in line with expectations. Simplicity in process requirements, very clear technical and administrative requirements, certainty of letter completion time, service products are very important, process and service products are very safe, very quick to respond, infrastructure very adequate, the location is very strategic so it is very easy to access, the officers are very friendly in providing services, the environment is very beautiful and healthy.